Elderly Hygiene Status in Rural Areas of Golestan Province in Iran - Hashem Heshmati; Naser Behnampour; Mohammad Hosein Haji-Ebrahimi; Abdorrahman Charkazi; Zahra Asadi; Anita Dehnadi (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: The aim of this study was to investigate elderly "hygienestatus" in Golestan provice (MaravehTapeh) in Iranian ordertoapply such information for health policy makers toplan appropriate health programs. Methods & Materials: In This descriptive-analyticalstudy, 119 males and females rural elderly over 60 years of age (mean 67.53±5.64) were selected through multi-stage sampling. Mean scores of hygiene status obtained on the basis of current questionnaire. Data were collected, completed through home interviews and analyzed via SPSS 17. Results: The mean age was 67.53±5.64 years. Score mean of “hygiene” status on the basis of current questionnaire was 60.59±16 (out of 100).There were not statistically significant relation between "hygiene status" and age, gender, education, job and living conditions But there was statistically significant difference between “hygiene status” and marital status. Conclusion: Present “hygiene status” of elderly is not desirable. As elderly population is growing more and more, undesirable hygiene and its consequences will create health problems. Appropriate educational planning initiations from health policy makers should be considered for such tar get population in Iran.